2004
DOI: 10.1097/01.tp.0000100684.59784.ff
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil reduces deterioration of renal function in patients with chronic allograft nephropathy

Abstract: Treatment with MMF reduced the progressive deterioration of renal function in patients with CAN, independently of the blood levels of CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Renal function as judged by Cockcroft-Gault GFR remained stable during the (median) 36 months of follow-up while the slope of the GFR improved. In 65 patients whose CyA levels had remained unchanged during follow-up, there was a reduction in the rate of loss of GFR [69]. Both of these studies are suggestive that the addition of MMF was responsible for ameliorating transplant function since the CyA levels and exposure remained unchanged.…”
Section: Mmfmentioning
confidence: 75%
See 2 more Smart Citations
“…Renal function as judged by Cockcroft-Gault GFR remained stable during the (median) 36 months of follow-up while the slope of the GFR improved. In 65 patients whose CyA levels had remained unchanged during follow-up, there was a reduction in the rate of loss of GFR [69]. Both of these studies are suggestive that the addition of MMF was responsible for ameliorating transplant function since the CyA levels and exposure remained unchanged.…”
Section: Mmfmentioning
confidence: 75%
“…Furthermore, it is unclear whether it is the addition of MMF per se which results in improved outcome or the reduction/withdrawal of CNI. This latter question has in part been addressed by two studies, carried out by Henne et al [68] and the Spanish Cooperative Study Group of Chronic Allograft Nephropathy [69]. The report by Henne et al in children with CAN exposed to 1.2 mg/m 2 of MMF without a change in CNI level showed a favorable allograft functional outcome at the price of significant (mainly gastrointestinal) side effects.…”
Section: Mmfmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that this improvement is related to the superior immunosuppressive activity of these drugs that allow a reduction in the incidence of not only acute rejection [11,12], but also subclinical rejection [13,14]. Furthermore, it has been suggested that both treatments may decrease the rate of progression of chronic allograft nephropathy (CAN) [13,15,16]. This tendency for a better preservation of renal function became more evident after the introduction of sirolimus.…”
Section: Immunosuppressive Treatment and Renal Functionmentioning
confidence: 97%
“…The Spanish Cooperative Study Group of Chronic Allograft Nephropathy prospectively explored the potential therapeutic role of MMF in patients diagnosed with CAN [22]. One hundred-twenty patients with biopsyproven CAN on double or triple therapy with CsA were treated with MMF.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%